Data Protection in Zimbabwe with Reference to the Covid-19 Pandemic and International Law - Otto Saki (Potchefstroom Electronic Law Journal)
The corona virus that caused the COVID-19 disease defied geographical boundaries, spreading faster than the measures to contain its transmission. The processing of personal health-related data became widespread as a measure to respond to the pandemic. This triggered new concerns about the possibility of there being a data crisis. Individuals suspected to be infected by COVID-19 were forced to undertake mandatory testing that involved the collection of health-related data. To limit the spread of the disease, the collection of personal data extended to secondary contacts. Personal health-related data are very prone to abuse, and this data included secondary data inconsistent with initial collection purposes. Admittedly, such risks are not new. Prior to the pandemic, health-related data were processed through electronic health (e-health) platforms. The health-related data processing methods during the pandemic were insufficient to meet the data protection principles of consent, transparency, purpose and storage, potentially violating the right to privacy. Globally, expectations are that countries should have data protection laws informed by established principles regulating the processing of personal data. While, Zimbabwe had not enacted the Cyber and Data Protection Act (CDP Act), which lists some of the data principles, this paper relies on existing laws to determine whether Zimbabwe is still abiding by constitutional and international human rights standards in protecting personal data privacy. The paper examines the development of data principles and their application in Zimbabwe in respect of health-related data protection during the pandemic. The paper 1) analyses the existing laws and their protection of personal health-related data; 2) explores the incorporation of data principles in COVID-19-related responses including in national laws as informed by international laws; and 3) highlights the gaps in both law and practice as they relate to the handling of personal health-related data in Zimbabwe during the pandemic. The paper concludes that even if the existing laws on data privacy were not comprehensive and even if the CDP Act came too late, the global regulations, the sectoral laws and other guidance accessible to Zimbabwe in responding to the pandemic would have sufficed to avert a data pandemic during the health pandemic and allowed Zimbabwe to be compliant with international data protection standards.